Celebrity Endorsement-Is It The Only Survival Recipe for Marketers? - Sharma, Smita (Indian Journal of Marketing, 2006)
Celebrity salespersons are a common calling card of brands these days. A celebrity is used to impart credibility and aspirational values to a brand. Recently we have seen a strong emergence of celebrity-endorsed campaigns in Indian advertising. Experts believe that when there is dearth of fresh and creative ideas, celebrity endorsed campaigns are used as the alternatives. Advertisers use endorsers to add excitement and glamour to their brands. Basically, celebrity endorsements give a brand a touch of glamour, and the hope that a famous face will provide added appeal and name recognition in a crowded market.But there’s another side also. Celebrities come with a load of liabilities that are hard to ignore. Whether a client uses a celebrity or not, the job of advertising isn’t reduced. Celebrity endorsed advertising should be accompanied by a powerful idea.